2004
DOI: 10.2134/jeq2004.1647
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Effect of Fumigation on Short‐ and Long‐Term Nitrogen Mineralization and Nitrification in Different Soils

Abstract: The effect of soil fumigation on N mineralization and nitrification needs to be better quantified to optimize N fertilizer advice and predict NO(-)(3) concentrations in crops and NO(-)(3) leaching risks. Seven soils representing a range in soil texture and organic matter contents were fumigated with Cyanamid DD 95 (a mixture of 1,3-dichloropropane and 1,3-dichloropropene). After removal of the fumigant, the fumigated soils and unfumigated controls were incubated for 20 wk and N mineralization and nitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…To assess the effect of fumigant treatments on nitrification, an S-shaped function was fitted to the NO À 3 -N concentrations of treated soil samples (Zhang et al 2000;De Neve et al 2004) using the following equation:…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of fumigant treatments on nitrification, an S-shaped function was fitted to the NO À 3 -N concentrations of treated soil samples (Zhang et al 2000;De Neve et al 2004) using the following equation:…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that organic matter application increases biomass nitrogen, and contributes to yield increase. D-D promotes mineralization from biomass nitrogen (Neve et al, 2004). D-D suppresses nitrification from ammonia nitrogen (Neve et al, 2004).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…D-D promotes mineralization from biomass nitrogen (Neve et al, 2004). D-D suppresses nitrification from ammonia nitrogen (Neve et al, 2004). Therefore, much ammonia nitrogen in soil will be kept by D-D.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt to quantify the effect of fumigation on nitrogen mineralization and nitrification in different soils found that there was no correlation between fumigation and mineralization (Neve et al 2004). In a test to evaluate management systems based on inputs of varietal resistance, nematicide and K-fertilization, the highest yields were observed in the Temik/ Telone II/K-treated plots (Hadden et al 1991).…”
Section: Introductionmentioning
confidence: 99%